Splenic rupture in an extremely low birthweight infant - Jennifer Hammond; Jennifer DeFazio; Vincent Duron; Aaron Wallman-Stokes (Elsevier, 2020)
Splenic rupture is a rare event in preterm and term infants. Symptoms of splenic rupture include acute blood loss, abdominal distention, and hypotension. We present the case of a 24 4/7 weeks gestation male infant born in the setting of preterm premature rupture of membranes who developed splenic rupture at 24 hours of life. Initially, the infant was managed medically. As the symptoms of abdominal compartment syndrome worsened, a bedside exploratory laparotomy was performed. The infant died on day of life 16 after developing hyperkalemia and pulmonary hemorrhage during an exchange transfusion for profound hyperbilirubinemia. This is the first report describing the management of splenic rupture in an extremely premature infant.